On a system of nonlinear partial functional differential equations of different types - SIMON, László (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
We consider a system of a semilinear hyperbolic functional differential equation (where the lower order terms contain functional dependence on the unknown function) and a quasilinear parabolic functional differential equation with initial and boundary conditions. Existence of weak solutions for $t\in (0,T)$ and for $t\in (0,∞ )$ will be shown and some qualitative properties of the solutions in $(0,∞ )$ will be formulated. Mathematics Subject Classification (2010): 35M33.